Pengaruh Tingkat Upah, Tingkat Pendidikan, dan Kesehatan terhadap Produktivitas Tenaga Kerja di Provinsi Jambi - Sheilla Ghina Zahra; Zulfanetti; Etik Umiyati (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of wage levels, education levels, and health on labor productivity in Jambi Province during the period 2009–2023. Labor productivity refers to the ability of a worker to produce output within a certain period of time. This research employs a quantitative approach using time series data obtained from publications of the Central Bureau of Statistics (BPS). The analytical method used in this study is multiple linear regression analysis. The results show that, simultaneously, wage levels, education levels, and health have an effect on labor productivity in Jambi Province. Partially, education level has a significant effect on labor productivity, while wage level and health have no significant effect on labor productivity in Jambi Province.